Changing Landscape of Haemophilus influenzae Meningitis and Implication on Public Health - John Allonce; Mohammed Ahsan; Angelina Browne; Rebecca Witherell; Mark Rasnake (Case Reports in Infectious Diseases)
Haemophilus influenzae (H. influenzae) has evolved as a prominent pathogen, with nontypeable strains (NTHi) emerging as a leading cause of invasive disease, particularly among the elderly. Since the introduction of Haemophilus influenzae B (Hib) vaccine, invasive infection has shifted from children with Hib to the elderly with NTHi. NTHi affects those primarily with predisposing factors such as an immunocompromised state, CSF leakage, or ENT infections. We present two cases that emphasize the shift of invasive infection, risk factors, and elevated intracranial pressure (ICP) as a complication. Case 1. A 75-year-old female with a sudden onset of weakness and respiratory symptoms deteriorated rapidly. Imaging revealed mastoid effusion and ventriculitis, likely originating from otomastoiditis. Lumber puncture confirmed NTHi. ICU course complicated by elevated ICP prompted repeat lumbar puncture. The patient recovered after 8 days but not near baseline. Case 2. A 50-year-old female with altered mental status, headache, and ear pain exhibited signs of pansinusitis and pseudotumor cerebri. Elevated ICP was evident upon lumbar puncture, and NTHi was isolated in CSF and blood cultures. MRI of the brain showed prominent optic nerve sheaths and transverse sinus arachnoid granulations’ concern for underlying pseudotumor cerebri. Repeat lumbar puncture or ventricular drainage was deferred after discussion with neurosurgery. Diabetes was identified as a comorbidity. The patient’s condition improved after 14 days of antibiotics and dexamethasone. These cases emphasize the shifting landscape of H. influenzae meningitis, primarily driven by NTHi, especially among the elderly. Although NTHi infections were considered less invasive, recent epidemiology review indicated it as the leading cause of H. influenzae meningitis. With the increasing prevalence of NTHi and its increase in invasive patterns, it is crucial to implement vaccination strategies and develop new vaccines targeting NTHi.